PENGUKURAN DAN ANALISIS PRODUKTIVITAS PRODUKSI DENGAN METODE OBJECTIVE MATRIX (OMAX) DI PG.KREBET BARU MALANG - Raden Faridz; Burhan Burhan; Adelya Eny Wijayantie (AGROINTEK, 2011)
PG. Krebet Baru Malang is a firm that produces sugar. To evaluate productivity, it is necessary to measure it  in the right way and with the proper tool.  The result of this measurement can be a consideration and be one of factor for adding production fasility and workforce that support the firm activity.  The main problem that will be studied in this research are how to measure firm productivity and what plan that should be done so that the firm productivity will raise then.  Method used in this study is Objective Matrix (OMAX). Following is the procedure of OMAX: 1) to determine criteria of how to improve productivity, 2) to determine performance ratio, productivity objective, scoring, assesment and weighting 3) evaluation, and 4) planning for the future.  This study rusults productivity or PG Krebet Baru: 1,67(2006), 5,85 (2007) with index 250,28. In 2008 2,33 with index -60,17.  In 2009 it raises to be 2,66 with index 14,16. The material productivity gives the largest contribution in the firm productivity measurement (2007). The decline of the firm productivity (2008) caused by the decline of the using of material and the length of the milling day.  The firm productivity is rise in 2009. This increment was caused by the improvement of machine productivity.  Some plannings of how to raise the firm productivity are: the usage of raw material, time of machine operated, and the length of milling day to get 5  score of productivity.